2009
DOI: 10.9775/kvfd.2011.4476
|View full text |Cite
|
Sign up to set email alerts
|

Türk Yağlı Kuyruklu Koyun Irklarındaki Beta-Laktoglobulin Gen Tipleri

Abstract: SummaryThe genetic polymorphism of the β-lactoglobulin gene was investigated in 182 sheep of Turkish fat-tailed sheep breeds by using PCR-RFLP methods. In the study, two alleles (A and B) and three genotypes (AA, BB and AB) at β-lactoglobulin locus were observed. The most common genotype at the β-lactoglobulin locus was AB. The greatest frequency of allele A was detected in Tuj breed as 0.7188.Results of the present study show that genetic polymorphism exists in the Turkish fat-tailed sheep breed population us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
1
1
Order By: Relevance
“…Similar findings were obtained in Kıvırcık (0.7759), Gökçeada (0.7632), and Sakız (0.9756) sheep breeds by Elmaci et al (2006); Awassi (0.6316), Tuj (0.7188), Norduz (0.7059), and Güney Karaman (0.6552) sheep breeds by Sahin et al (2011).Similarly, Çelik and Özdemir (2006) reported that the A allele frequencies determined in Awassi and Morkaraman sheep were 0.63 and 0.56, respectively. Sahin et al (2011) showed that the BLG B allele was high in Dağlıç, Akkaraman, Karakaş, and Kangal sheep. This differs from the findings presented here in Norduz sheep.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar findings were obtained in Kıvırcık (0.7759), Gökçeada (0.7632), and Sakız (0.9756) sheep breeds by Elmaci et al (2006); Awassi (0.6316), Tuj (0.7188), Norduz (0.7059), and Güney Karaman (0.6552) sheep breeds by Sahin et al (2011).Similarly, Çelik and Özdemir (2006) reported that the A allele frequencies determined in Awassi and Morkaraman sheep were 0.63 and 0.56, respectively. Sahin et al (2011) showed that the BLG B allele was high in Dağlıç, Akkaraman, Karakaş, and Kangal sheep. This differs from the findings presented here in Norduz sheep.…”
Section: Discussionsupporting
confidence: 79%
“…AB genotype (0.70) in the study was the most common genotype in the Norduz breed. Similar results for the genotype of ovine BLG in Awassi, Dağlıç, Akkaraman, Karakaş, Norduz, Güney Karaman, and Kangal sheep breeds were reported by Sahin et al (2011).On the other hand, this study was inconsistent with the results reported for HWE by Sahin et al (2011).…”
Section: Discussioncontrasting
confidence: 63%
“…PCR was done according to the protocol 13,17 with minor modifications. The primer set of "forward; 5-TGGA TGGACCGGCGAGACAAGCGTCGAGATGCTGCTGGACATGGGGCTGAGCCATGTAATAATAGGACA CTCTGAAAGACGTAGAATCATGGGCGAGACCAATGAGCAGAGTGCTAAGAAGGCGAAGCGTGCTC TGGACAAAGGTATGACTGTTATCTTCTGCACCGGAGAGACCCTGGATGAACGCAAGGCCAATAACA CTATGGAGGTGAATATTGCTCAGC^TCGAGGCTCTTAAGAAGGAGATTGGAGAATCAAAGAAGTTA TGGGAGAACGTTGTAATGCCTATGAGCCGGTGTGGTCTATCGGCACGGGTGTGGTGGCCACACCG GAGCAGGCAGAGGAAGTCCATGTGGGACTCCGCAAATGGTTTGCGGAAAAGGTTTGCGCAGAAGG TGCGCAGCACATCCGCATCATCTATGGAGGGTCTGCCAATGGGAGTAACTGCGAGAAGCTTGGCCA GTGCCCGAATATCGACGGATTCCTCGTCGGAGGTGCTTCCCTCAAGCCGGA (Fig.…”
Section: Pcrmentioning
confidence: 99%